TYPOLOGY OF THE COSTUME FOR THE RECREATIONAL AND TOURISM - Артеменко, М. П.; Чепелюк, О. В.; Колосніченко, М. В. (Art and Design, 2020)
The aim of the research is to develop a typology of costume for the recreational and tourism sector and to determine the specifics of its design as a means of increasing the attractiveness of events and the formation of the tourist image of the region. The article uses typological and comparative-descriptive methods in identifying the characteristics of costumes used in the recreational and tourist sector and their classification according to the nature of contact with a tourist, purpose and other characteristics. The complex use of functional, ergonomic, figurative-stylistic analysis methods allowed to determine the specifics of the design design of the studied clothing. Costume design is considered as a means of increasing attraction and developing the recreational and tourist sphere. The main specific typological costume groups for this industry were identified and a structural-logical classification scheme was built according to the nature of the contact with the tourist/recreant, purpose, the ratio of utilitarian and artistic and aesthetic principles, the method of transmitting information about the tourist region/event and the type of creative source used. The specifics of designing a suit from the standpoint of aesthetic and ergonomic characteristics is determined. The scientific novelty of the work lies in the fact that for the first time the role of the costume in the field of tourism and recreation is updated, the development of which is one of the priority areas for the development of the economy of Ukraine as a whole and its areas. In addition, the types of costume in the recreational and tourist sphere were first identified and systematized and the features of its design were highlighted. The results obtained will allow us to optimize the process of conscious design and improve the quality of the art-shaped solutions of the costume in the recreational and tourism sector. It is also advisable to use the results of the study in the preparation of lecture courses in the educational process in the preparation of design specialists of various educational qualification levels.